Sleep patterns can predict onset of Alzheimer's disease. (2nd April 2019) - Palmer, Sarah
Abstract : A recent study has linked reduced amounts of deep sleep to the progression of Alzheimer's disease. Sarah Palmer discusses the study and advises how to handle sleep disturbances in those in more advanced stages of dementia.